(untitled) (International journal of artificial intelligence, 2026)
Speech is one of humanity's most remarkable means of communication. The methodology of developing speech is a crucial subject in linguistics and education, as well as in social relations. The evolution of ideas, the dissemination of cultural concepts, and the overall advancement of societies are deeply intertwined with the ways in which individuals express themselves. The art of structuring thoughts into clear, grammatically correct, and effective speech is essential not only for everyday communications but also for academic and professional achievements.